International copyright and neighbouring rights : the Berne Convention and beyond - Ricketson, Sam; Ginsburg, Jane C. (Oxford University Press, 2010)
International copyright and neighbouring rights : the Berne Convention and beyond. Vol. 2 | WorldCat.org